Marabastad’s informal traders: a struggle for survival - Brandt, Oliver (ERDKUNDE, 2002)
The study was conducted to further explore the link between formal and informal business and the heterogeneity of the informal traders in Marabastad as a group. Data was analysed by means of a SPSS cluster analysis to reveal major groupings of hawkers in both research foci. It was found that only a small number of hawker activities could be classified as growth enterprises whereas for the majority of street vendors trading is a survival strategy. The link to formal business was not as strong as reported in other studies and no significant clustering of hawkers could be found in the statistical analysis. The findings pose a major challenge to policy-makers and role-players in Marabastad because it will be difficult to promote informal enterprises without a significant reduction of their number. The fact that the informal economy consists mainly of survival enterprises calls into question the overall developmental role often posited for the informal sector: at least in Marabastad.